Community Based Study of Socio-demographic Determinants of Low Birth Weight Baby in Rural Area of Western Maharashtra - Avachat, S S; Phalke, V D; Kambale, S V (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: There is only marginal reduction in proportion of low birth weight babies during last fifteen years. Birth weight is influenced by number of social, economic and demographic factors. The present study was conducted in a rural community to estimate the magnitude of low birth weight and to study the associated sociodemographic factors. Methods: A cross sectional community based study was conducted in six randomly selected villages. Six hundred and fifty two under five children were randomly selected from these villages and data was collected by interviewing mothers of thesechildren with the help of predesigned questionnaire. Information pertaining to age, economic status of mother, antenatal care, birth spacing was collected and significance of these determinants was obtained by appropriate statistical tests. Results: The proportion of low birth weight babies in present study, conducted in a rural community was 18.1%. Significantly large proportion of low birth weight children were born to mothers belonging to lower socioeconomic status and lower educational status. 51% babies were born to mothers with age below 20 years and 25% babies were born with birth interval less than two years. Conclusions: Maternal age, socioeconomic status, antenatal care and short birth spacing are the significant maternal determinants of the birth weight of the baby. Interventions relating to these determinants can reduce the problem of low birth weight in rural area DOI: http://dx.doi.org/10.3126/njog.v9i2.11771